Whole egg consumption compared with yolk-free egg increases the cholesterol efflux capacity of high-density lipoproteins in overweight, postmenopausal women. Issue 3 (7th June 2019) - Sawrey-Kubicek, Lisa; Zhu, Chenghao; Bardagjy, Allison S; Rhodes, Christopher H; Sacchi, Romina; Randolph, Jody M; Steinberg, Francene M; Zivkovic, Angela M
ABSTRACT: Background: Postmenopausal women are at higher risk for cardiovascular disease (CVD) than their younger counterparts. HDL cholesterol is a biomarker for CVD risk, but the function of HDL may be more important than HDL cholesterol in deciphering disease risk. Although diet continues to be a cornerstone of treatment and prevention of CVD, little is known about how diet affects the functionality of HDL. Objectives: The aim of this study was to characterize the effects of whole eggs compared with yolk-free eggs on HDL function and composition in overweight, postmenopausal women and determine how changes in HDL composition are related to HDL functional parameters. Methods: The study was a 14-wk, single-blind, randomized crossover dietary trial with two 4-wk intervention periods in 20 overweight, postmenopausal women. The crossover treatments were frozen breakfast meals containing 100 g of liquid (∼2) whole eggs compared with 100 g of (∼2) yolk-free eggs per day, separated by a 4-wk washout. Fasting blood samples were taken at the beginning and end of each treatment period to determine the effects on HDL composition and function. Results: Cholesterol efflux capacity increased in the whole-egg treatment (mean ± SD percentage change: +5.69% ± 9.9%) compared with the yolk-free egg treatment (−3.69% ± 5.3%) ( P  < 0.01), but there were no other significant changes in HDL functions or antioxidant or inflammatory markers. ApoA-I, total cholesterol (TC), LDL cholesterol, and HDL cholesterol also did not change in response to the egg treatment. Conclusions: The consumption of 2 whole eggs/d by overweight, postmenopausal women showed a significant increase in cholesterol efflux capacity. This increase in cholesterol efflux capacity was seen without significant changes in apoA-I, TC, LDL cholesterol, or HDL cholesterol, supporting the idea that HDL function rather than HDL cholesterol should be addressed in this population. This trial was registered at clinicaltrials.gov as NCT02445638.